Effect of Intrinsic ZnO Sputtering Parameters on the Cell Efficiency of Cu(In,Ga)Se-2 Solar Cells - Lee, Kkotnim; Son, Yu-Seung; Jeong, Jeung-hyun (WILEY-V C H VERLAG GMBH, 2015)
We investigated the effect of adding oxygen (O-2) gas to argon (Ar) gas and varying the sputter target power during intrinsic ZnO sputtering on the photovoltaic performance of Cu(In,Ga)Se-2 (CIGS) solar cells. Sputtering powers of 50, 100, 150W were used in conjunction with an O-2 fraction of 0% or 2% in the sputtering gas. Both increasing the power and adding oxygen improved the photovoltaic conversion efficiency, although the effect of the latter was more pronounced. The results showed that the open-circuit voltage, short-circuit current density, and fill factor were all improved, and the series resistance was reduced. Electroluminescence spectroscopy and electron-beam-induced current analysis showed that adding oxygen and increasing the power not only improved the CdS/CIGS junction properties, but also the CIGS bulk properties. The current-voltage characteristics at low temperature indicated that adding oxygen and increasing the power facilitated local secondary diode formation around the CIGS surface. It was also revealed that the sodium doping concentration was enhanced by oxygen addition and increased power, with this enhancement being larger for the former. The improvements in the CdS/CIGS junction and CIGS bulk properties were therefore tentatively attributed to an enhancement of the Na doping level.
Keywords: THIN-FILMS